(3LeY GdahGFO GdefJNHI GdUMjMI ef GdNhGU GdeLQHIs - (3nCoHh GdnYdGA GdEnjGOj , RgQ Hf YHO Gdedc Hf eMeO Hf eQhGf GHf RgQ, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje LeY GdahGFO GdUMjMI GdeLQHI, bO Cdag GdhRjQ GdMcje CHhGdYdGA GHf RgQ HGH GdCdhGf (B: (3EfSGf , TYQ GdEfSGf EPG HVQHg TF UZQg, hEPG Ydb Se GejJ Ydi Sf hLYg Scf hLYgG s
(3BNQgG (B:s
(3MQa GdjGA, jHQhM(B: (3gh Tcd Ydi gjFI GdEfSGf jchf ai HdGO GdCJQGc, jchf JMJ GdCQV, hdGjbdYg EdG GdcdH, hQHeG eGJ hbJ bdYgJe GdcJGH s
(3GfXQgG eY GdeQTO ddQGRi Qbe (B"730"s
(3GdfSNI HgG MhGTs
(3fSNI SGOSIs
(3cGdSGHbI JeGekG hojQLM Cf Jchf EMOGgeG eUhQI ef GdCNQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B76 s
Keywords: (3GdWHs